2017
DOI: 10.1051/alr/2017010
|View full text |Cite
|
Sign up to set email alerts
|

Length–weight relationships for 22 crustaceans and cephalopods from the Gulf of Cadiz (SW Spain)

Abstract: Life history traits are available for many fish species in different regions, but less so for invertebrates such as cephalopods and crustaceans, though, they are increasingly needed for implementing an ecosystem-based approach. Recent food web modelling in the Gulf of Cadiz has identified invertebrates as keystone groups. However, information on life history traits of such groups remains incomplete in this region. To fill this knowledge gap, we report length-weight relationships for 12 cephalopods and 10 crust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Although LWR is widely used and known for fish, it is poorly understood for non-fish species 5 . In fact, cephalopods particularly should be investigated carefully for LWR studies as they have unique life history traits such as semelparity, sexual dimorphism (extreme in some species e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although LWR is widely used and known for fish, it is poorly understood for non-fish species 5 . In fact, cephalopods particularly should be investigated carefully for LWR studies as they have unique life history traits such as semelparity, sexual dimorphism (extreme in some species e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The latter study also shows that, at least in the Adriatic Sea, S. orbignyana has group-synchronous ovulation and the species is most probably an intermittent terminal spawner. It was found that weight-length relationships of both sexes exhibit slower relative growth in weight than in length (b = 2.46 in males and b = 2.62 in females), which corresponds to the growth patterns seen in the Gulf of Cadiz, although the scaling exponent b reaches only 2.38 in the latter case (Torres et al, 2017).…”
Section: Sepia Elegans and S Orbignyanamentioning
confidence: 72%
“…Weight-length relationships for E. cirrhosa and E. moschata in South West Iberian waters (Gulf of Cádiz) were similar, although the scaling exponent b was lower in E. cirrhosa (b = 2.34) than in E. moschata (b = 2.70) (Torres et al, 2017).…”
Section: Life Historymentioning
confidence: 86%
See 2 more Smart Citations